21st Leadership styles - Villace Fernández, Carlos (Universidad Pontificia Bolivariana, 2023)
The 21st century led to a new concept of leadership as the result of new political,economic,social and cultural scenarios,and one of the most relevant factors is the globalized environment to which organizations and institutions are involved. In this stage new leadership,networking,charismatic,changing,and global requirements of organizations and institutions are addressed. © 2023,Universidad Pontificia Bolivariana. All rights reserved.
[Liderazgos del siglo XXI]